Experimental evidence for female mate choice in a noctuid moth. (September 2021) - Zweerus, Naomi L.; van Wijk, Michiel; Schal, Coby; Groot, Astrid T.
Abstract : Sexual signal evolution is shaped by whether only one or both sexes execute mate choice. When mate choice by both sexes is considered, the same signalling modality is generally inferred for males and females. In the noctuid moth Chloridea ( Heliothis ) virescens (Lepidoptera: Noctuidae), both sexes may be signallers and responders, as both emit a sex-specific pheromone. Male mate choice is based on the female sex pheromone, perceived via the antennae, and has been well documented. However, whether females choose partners and whether their choice is based on the male pheromone are unknown. Since female mate choice is expected when males vary in quality, we reared males on two different larval diets that affected their size, which correlated positively with their fitness. When given a choice, more females mated with larger than with smaller males, and these females produced more eggs and larvae. Female choice was not affected by the absolute amount or composition of the male pheromone. Moreover, we found that antennaless females mated as readily as intact females, indicating that antennal sensory input is not required for females to mate. To determine whether females make an active choice, we studied courtship behaviour in detail and observed that females determined the outcome of courtship by moving away from the male (avoidance) or by facilitating copulation with an abdominal bend (acceptance). Additionally, we discovered that tactile sensory stimuli may be involved during courtship. Because tactile interactions may mediate contact-based (chemical) communication, we also investigated putative pheromone components on moth legs, but found no differences between the sexes. Together, our study is the first comprehensive investigation of female mate choice in a heliothine moth. Highlights: In the noctuid moth Chloridea virescens, females mated more with larger males. Larger males were higher quality mating partners than smaller males. The quality and quantity of male hairpencil pheromone did not explain female choice. Females showed avoidance and acceptance behaviour, and thus chose partners actively. Male traits other than the hairpencil pheromone likely affect female choice.